Chemical Quality of Culled Duck Meatball (Anasplathyryncos) Substituted with Edamame Flour (Glycine max (L) Merril) Filler - Agus Hadi Prayitno; T H Rahman (Indonesian Center for Animal Research and Development (ICARD), 2020)
This study aimed to determine the effect of edamame flour filler substitution on the chemical quality of culled duck meatballs. The research material consisted of culled duck meat, tapioca flour, edamame flour, albumen, garlic, onion, salt, pepper, monosodium glutamate, sodium tripolyphosphate, and ice. The edamame flour filler substitution treatments were P0 (0%), P1 (5%), P2 (10%), P3 (15%), and P4 (20%) from total filler. Each treatment consisted of five replications. The parameters which tested were moisture, protein, fat, fiber, and ash contents. Data on chemical quality results were analyzed by analysis of variance using completely randomized design and if there was significantly different (P<0.01), then it’ll be further tested by the Duncan's New Multiple Range Test. Results showed that the substitution of edamame flour filler starting from the level of 5% was significantly affected water content, protein, fat, fiber, and ash of culled duck meatballs. Edamame flour can be used as a filler substitution up to 20% level by giving a good effect on increasing the meatball protein content, but also having a negative impact with increasing the fat content of culled duck meatballs.